2021
DOI: 10.1016/j.ajur.2020.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The robot-assisted ureteral reconstruction in adult: A narrative review on the surgical techniques and contemporary outcomes

Abstract: Despite the rapid increase in the use of robotic surgery in urology, the majority of ureteric reconstruction procedures are still performed using laparoscopic or open approaches. This is primarily due to uncertainty regarding the advantages of robotic approaches over conventional ones, and the unique difficulty in identifying the specific area of interest due to the lack of tactile feedback from the current robotic systems. However, with the potential benefits of minimal invasiveness, several pioneering report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Most of the current studies on minimally invasive ureteroplasty in BMG have focused on the robot-assisted procedure ( 6 , 7 , 18 , 19 ). Arora et al reported no data for recurrence during the 6-month follow-up period ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the current studies on minimally invasive ureteroplasty in BMG have focused on the robot-assisted procedure ( 6 , 7 , 18 , 19 ). Arora et al reported no data for recurrence during the 6-month follow-up period ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The first BMG ureteroplasty in humans was described in 1999 (4). However, interest in this technique has renewed over the past decade, and the technique is now reported in numerous articles regarding its utility in open and robotic approaches (5)(6)(7). Unfortunately, there is a lack of papers dedicated to the laparoscopic BMG ureteroplasty of the complex upper ureteral stricture, being necessary to build a confident opinion on the pros and cons of different approaches (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Robot-assisted ureteral reimplantation has comparable outcomes to those with open and laporoscopic approaches in the hands of experienced robotic surgeons [1] , [2] . Ureteral reimplantation is commonly performed in the management of ureteral strictures and after ureteral injuries.…”
Section: Introductionmentioning
confidence: 99%